Alternative methods for pharmacological research on the action mechanisms of natural products used in the treatment of type 2 diabetes: a systematic review - Espinoza-Hernández, Fernanda Artemisa; Martínez-Medina, Samantha; Mata-Torres, Gerardo; Cabello-Hernández, Christian Alan; Andrade-Cetto, Adolfo (Frontiers in Pharmacology, 2026)
Type 2 diabetes (T2D) is a complex metabolic disorder characterized by alterations in multiple pathways of carbohydrate and lipid metabolism. Due to the involvement of a network of dysfunctional enzymes contributing to hyperglycemia, ethnopharmacological research has increasingly focused on identifying new drugs that can improve clinical outcomes. In this context, animal models have remained essential for evaluating naturally occurring molecules with potential hypoglycemic effects. However, the scientific community has recently emphasized the need for alternatives to animal use in biomedical research. This review aims to highlight the alternative approaches employed in recent years to discover natural products with therapeutic potential for T2D, emphasizing the most relevant mechanisms of action and pharmacological targets. A systematic search of original articles published between 2019 and 2024 in the PubMed, Scopus, and Web of Science databases identified nine key mechanisms: inhibition of carbohydrate breakdown, modulation of glucose absorption and uptake, enhancement of glucose storage, suppression of glucose production, targeting insulin resistance factors, insulin sensitization, β-cell protection, improvement of lipid metabolism, and sirtuin modulation. During this period, approximately 45% of the studies employed predominantly in vitro approaches involving enzymes, transporters, and receptors central to the pathophysiology of T2D, while in silico studies displaced in vivo studies, increasing their percentage from 16% to 36% in the last year. This review presents a new classification of action mechanisms and compiles the most representative types of assays that have been carried out in recent years to address the most studied pharmacological targets. Therefore, it is expected that this review serves as a foundation for future investigations into underexplored mechanisms particularly insulin sensitization and pancreatic β-cell preservation that may offer greater therapeutic impact.